Quantifying the Environmental and Economic Performance of Remote Communities - Filer, Jamie; Schuldt, Steven (European Journal of Sustainable Development, 2019)
Remote communities such as oil production sites, post-disaster housing camps, and military forward operating bases (FOB) are often detached from established infrastructure grids, requiring a constant resupply of resources. In one instance, a 600-person FOB required 22 trucks per day to deliver necessary fuel and water and remove generated wastes. This logistical burden produces negative environmental impacts and increases operational costs. To minimize these consequences, construction planners can implement sustainability measures such as renewable energy systems, improved waste management practices, and energy-efficient equipment. However, integration of such upgrades can increase construction costs, presenting the need for a tool that identifies tradeoffs among conflicting criteria. To assist planners in these efforts, this paper presents the development of a novel remote site sustainability assessment model capable of quantifying the environmental and economic performance of a set of infrastructure alternatives. Through field data and literature estimates, a hypothetical FOB is designed and evaluated to demonstrate the model’s distinctive capability to accurately and efficiently assess construction alternatives. The proposed model will enable construction planners to maximize the sustainability of remote communities, creating sites that are more self-sufficient with reduced environmental impacts. Keywords: Sustainability, infrastructure, remote communities